Evaluation of antennas performance with FCC and common spectral mask for UWB localization - Kingsakda, Vongkeo; Satahack, Phonepaseuth; Mingmanee, Sirapop; Promwong, Sathaporn (My University, 2015)
Antennas which are used to transmit and receive ultra wideband impulse radio (UWB-IR) signals should be able to accomodate its large bandwidth. Moreover, the signals should not be distorted too much when they pass through the antennas. Therefore, the transfer function of antennas should be known the performance. The indoor and the outdoor localization are usually evaluated by using the extension of Friis' transmission formula. However, it is not directly application to UWB transmission systems. This paper are presentation, the characterization of UWB antennas performance that takes into account the transmission signal waveform, its distortion due to the antennas, and the receiver. Since the antennas are significant pulse-shaping filters in UWB, various kinds of antennas are experimentally examined, especially focusing on the UWB template waveform.
Keywords: antenna; Friis' transmission formula; impulse radio (IR); indoor localization; ultra wideband (UWB)